Etapas del tratamiento documental de imagen en movimiento para televisión. - Nuño Moral, María Victoria; Caldera Serrano, Jorge (Revista General de Información y Documentación, 2002)
This article deals with the stages of documentary processing for audiovisual documentation management in informative television programs. Before introducing a new model, the main contributions made by both national and international professionals are reviewed. The viewing, summary and indexing stages are developed in a model valid for local, regional and national television.
Keywords: Television archives; Data processing; Audiovisual documentation; Informative; programs